Making paddy cultivation profitable in Orissa - Das, Sandip (Indian Farming, 2015)
A farmer from Jajpur district in Orissa has turned his rice growing agricultural land into a profitable commercial business by taking up fisheries and cultivation of fruits and vegetables. Because of the unique integrated rice-fish system, developed by the Central Rice Research Institute, farmers are making it sure that rice cultivation besides providing food security also guarantees livelihood security.